ANALISA SIFAT FERROMAGNETIK MATERIAL MENGGUNAKAN METODE MONTE CARLO - Mardiansyah, Dedi (Edu Research, 2013)
Experiment conducted by the Curie-Weiss has described the phenomenon of changes in the magnetic susceptibility of a material to temperature changes, but there is no clear simulation. Hence, simulations and graphs to explain that phenomenon is needed. Simulation and graphics created by mathematical equations that have been there from the discussion about the microscopic properties of magnetic materials, particularly of ferromagnetic materials. This aided manufacturing simulation using the Pascal programming language BorlandDelphi compiler. Used in the manufacture of this simulation Monte Carlo method, which utilizes the Metropolis algorithm as its phases and Ising models as zoom.